Formação de preços e finanças comportamentais: um estudo empírico no mercado futuro de cacau - Pereira, Elenildes Santana (2009)
This work aimed to exam the formation of future market prices of cocoa traded on the New York Stock Exchange, under the view of the volatility from January 1997 to August 2008, since the future market is playing an important role in making decision, focusing on maximizing returns. In a particular way, the study of volatility is an essential tool in this market, especially for pricing of assets and risk management. For this, three variants of the class of models of auto-regressive conditional heteroscedastic (ARCH), GARCH, EGARCH and TARCH, were used and showed characteristics of models that take into account the changing variance over time. The conditional variance provided by these models was used as a proxy for the volatility of returns on cocoa. The results demonstrated the persistent behavior of volatility in the period in question. This persistence indicates that the shocks on the volatility will last for long. We found evidence of inconsistency with the hypothesis of efficient markets that has the responsibility of future returns to past returns, since there is presence of auto-regressive terms in waste, captured by the ARCH effect, and also by the possibility of behavioral biases (depending on of information asymmetries in the reactions between positive and negative). The theories of modern finances predict that investors have homogeneous expectations (investors have the same information and determine the fair value for the same active base). It would therefore not be expected to have excessive volatility in the future market of the commodity cocoa, then there would be no difference of opinion among investors. However, the results showed that the volatility implies in the formation of the price of cocoa, making it impossible to explain it by traditional theories of finance, and indicate that this volatility may also result from decisions of investors from the psychological aspects that arise when forming their beliefs and preferences that, in turn, are reflected in expectations. Thus, the results suggest that Behavioral Finance can contribute to the understanding of the formation of future market prices for cocoa.